STRENGTHENING CHARACTER EDUCATION BASED ON RELIGIOUS MODERATION IN ISLAMIC RELIGIOUS EDUCATION LEARNING MATERIALS IN THE SCOPE OF EARLY CHILDHOOD: A CASE STUDY IN ABA MUHAMMADIYAH KINDERGARTEN YOGYAKARTA (International Conference on Social and Islamic Studies, 2022)
Yogyakarta is known as the city of student culture, rich in culture, especially rich in educational culture. However, it is the opposite. Based on data from the Yogyakarta City Education Agency (DIKPORA), namely the prevalence of juvenile delinquency, klitih (slashing people), bullying, bullying, and the decline in reading and learning culture, affect the number of ignorance and unemployment in the Special Region of Yogyakarta. This scientific paper aims to strengthen character education based on Religious Moderation in Islamic Religious Education (PAI) lessons at the Kindergarten (Kindergarten) level. The setting of this research is in TK ABA Muhammadiyah Yogyakarta, the location of the place, precisely in the Special Region of Yogyakarta. The setting was chosen in the ABA Muhammadiyah Kindergarten, Yogyakarta, with reasons according to the theme of the discussion. That is, they want to explore deeply character education starting from the kindergarten level so that later it will be easier to educate them at the school level afterward. The research informants consisted of teachers, kindergarten leaders, and parents of kindergarten students. The selection of subjects was carried out by purposive sampling technique, namely the researcher believed in the data and findings presented by the informants or research subjects. The method used by the researcher is a case study-based qualitative research, meaning that the researcher meets directly with informants, objects, and data at the research location. Researchers facilitate data collection by using interview techniques, observation, and documentation. Data analysis was performed by data display, data reduction, data presentation, and data verification. To avoid and avoid claims, and the lack of data, researchers are strengthened and sharpened by the validity of the data, namely by interview triangulation and documentation. The results of the study found that the prevalence of juvenile delinquency, klitih, and laziness in learning were interrelated with strengthening the character taught from early childhood, especially in kindergarten-level children. This strengthening is supported by Islamic religious education lessons, focusing on religious moderation material. It can be seen that because of certain conflicts, are still related to the problems that exist in the community in Yogyakarta. The novelty offered by the researcher is PAI material in the chapter on religious moderation which is effective in strengthening character education in Yogyakarta.